Systematic review and meta-analysis of diagnostic accuracy of loop-mediated isothermal amplification (LAMP) methods compared with microscopy, polymerase chain reaction and rapid diagnostic tests for malaria diagnosis. (September 2020) - Picot, Stephane; Cucherat, Michel; Bienvenu, Anne-Lise
Highlights: A systematic review and meta-analysis of the diagnostic accuracy of loop-mediated isothermal amplification (LAMP) tests was performed. LAMP tests were compared with microscopy, polymerase chain reaction and rapid diagnostic tests. Sixty-six studies were included, leading to 30, 641 individual LAMP tests. The diagnostic odds ratio of LAMP versus microscopy was >900. The impact of LAMP for controlling malaria is expected to be important. Abstract: Background: Diagnosis is a challenging issue for eliminating malaria. Loop-mediated isothermal amplification (LAMP) could be an alternative to conventional methods. This study aimed to evaluate the diagnostic accuracy of LAMP for malaria compared with microscopy, polymerase chain reaction (PCR) and rapid diagnostic tests (RDTs). Methods and design: MEDLINE, Web of Science and Scopus were searched from inception to 1 July 2019. Prospective and retrospective, randomised and non-randomised, mono-center and multi-center studies, including symptomatic or asymptomatic patients, that reported one LAMP method and one comparator (microscopy, RDT or PCR) were included. PROSPERO registration number: CRD42017075186. Results: Sixty-six studies published between 2006 and 2019 were included, leading to the analysis of 30, 641 LAMP tests. The pooled sensitivity of LAMP remained between 96% and 98%, whichever the comparator. The pooled specificity of LAMP was around 95%, but was a little higher if the best PCR studies were considered. The AUC was found to be >0.98, whichever the subgroup of studies was considered. Diagnostic odds ratio (DOR) was found to be around 1000 for all subgroups, except for Plasmodium vivax . Conclusion: This meta-analysis confirmed that the LAMP method is robust for diagnosing malaria, both in symptomatic and asymptomatic people. Thus, the impact of LAMP for controlling malaria is expected to be important.